Click‐Crosslinked Injectable Gelatin Hydrogels. Issue 5 (25th January 2016) - Koshy, Sandeep T.; Desai, Rajiv M.; Joly, Pascal; Li, Jianyu; Bagrodia, Rishi K.; Lewin, Sarah A.; Joshi, Neel S.; Mooney, David J.
Abstract : Injectable gelatin hydrogels formed with bioorthogonal click chemistry (ClickGel) are cell‐responsive ECM mimics for in vitro and in vivo biomaterials applications. Gelatin polymers with pendant norbornene (GelN) or tetrazine (GelT) groups can quickly and spontaneously crosslink upon mixing, allowing for high viability of encapsulated cells, establishment of 3D elongated cell morphologies, and biodegradation when injected in vivo.